Decerebrate posturing following traumatic brain injury: MRI findings and their diagnostic value. Issue 3 (March 2015) - Woischneck, D.; Skalej, M.; Firsching, R.; Kapapa, T.
<x xml:space="preserve">Abstract</x> Aim To determine the pathomorphological and clinical background to decerebrate posturing in humans following serious traumatic brain injury. Materials and methods One hundred and twenty patients who had been unconscious for more than 24 h underwent diagnostic MRI within 8 days after trauma. The presence of decerebrate rigidity as the clinical parameter was correlated to MRI findings, such as traumatic lesions in defined brain areas. Significance was presumed as p < 0.05. Results On the day of MRI 43 (36%) patients exhibited decerebrate posturing: 19 (23%) cases were unilateral and 24 (77%) bilateral. There was a significant correlation between midbrain lesions and the presence of rigidity. If a midbrain lesion was found in the absence of pontine lesions, decerebrate rigidity could be concluded (p < 0.05). There was no significant correlation to the rigidity in the case of midbrain lesions accompanied by pontine lesions, and no correlation to the rigidity could be detected for other regions of the brain. Both the occurrence of decerebrate posturing and the detection of brainstem lesions at MRI correlated with the Glasgow Outcome Scale. The combination of both parameters improved the probability of predicting the outcome. Conclusion The rate of decerebrate posturing increases significantly in the presence of midbrain lesions. The presence of pontine lesions appears to be of secondary importance. The chances of predicting the Glasgow Outcome Scale are improved by the combination of clinical information (decerebrate posturing) and radiological parameters (type of brainstem lesion).